PENGARUH MODEL PEMBELAJARAN MEDIA GAMBAR TERHADAP HASIL BELAJAR ROLL DEPAN SENAM LANTAI (STUDI PADA SISWA KELAS VIII SMP KARTIKA IV-11 SURABAYA) - ALAMSYAH, NUR (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The purpose of this study is to find out: (1) the influence of media images learning model to the learning result of 8th graders Kartika IV-11 Junior High Shcool Surabaya, (2) how big is the differences on the influence of learning models media images to the results of forward roll gymnastics. Objectives of this study were students of class VIII Kartika IV-11 junior high shcool Surabaya taken as many as 36 students of class VIII C and 36 students of class VIII D. Methods in the analysis of this data is quantitative descriptive approach, while the data collection is done by testing the forward roll gymnastics with aspects of the observed include: the starting position, the position of the hands and feet, roll position, the end position. The conclusion of this study are as follows: By calculation correlation t test with significance level 0.05%, In the results of the different test between groups show that ttest 1.807 < 2.000 ttable. It can be concluded that didn’t influence on the application of image media learning model the learning outcomes of the forward roll floor gymnastics class VIII-D Kartika IV-11 junior high school Surabaya.       Keywords: Learning Model Media Images, Forward Roll Gymnastics, Learning Outcomes, Junior High School.